2019
DOI: 10.1111/1365-2664.13473
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying parasitoid and predator controls on rice hopper eggs using a dynamic stage‐structured model and field data

Abstract: 1. Rice hoppers can cause devastation to rice crops in SE Asia via disease spread and direct feeding. Current regulation is through pesticides; however, a more sustainable approach is to use the natural enemies of the hoppers. Here, we show how the combination of a process-based model and field data can give insights into natural pest control, beyond those obtained through direct analysis of the field data.2. We use a stage-structured host-parasitoid model based on time-delay ordinary differential equations (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The presence of natural enemy's such as SPD, GMB, and LBB is crucial in regulating PH populations within their ecosystem [ [40] , [41] , [42] ]. The decline in populations of the WBPH during crop maturation is influenced by the regulation exerted by natural enemies, as noted by Kettle et al [ 43 ], and the changes in rice susceptibility as the plants mature, as observed by Horgan et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of natural enemy's such as SPD, GMB, and LBB is crucial in regulating PH populations within their ecosystem [ [40] , [41] , [42] ]. The decline in populations of the WBPH during crop maturation is influenced by the regulation exerted by natural enemies, as noted by Kettle et al [ 43 ], and the changes in rice susceptibility as the plants mature, as observed by Horgan et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that competition between nymphs at optimal temperatures contributes to WBPH population stability in rice and to the declines observed as the crop matures. Population regulation by natural enemies [ 37 , 47 , 48 ] and ontogenic changes in rice susceptibility [ 46 ] also contribute to the decline of WBPH populations during crop maturation. Our results indicate that current ambient temperatures in tropical Asia, that frequently surpass 30°C during extended periods [ 18 , 41 ], will reduce the potential for WBPH to attain outbreak densities.…”
Section: Discussionmentioning
confidence: 99%